Prevalence of gastrointestinal protozoa in pet and stray cats in the Klang Valley, Malaysia - Tan, Li Ping (2019)
Gastrointestinal protozoa that are commonly reported to cause diarrhea in cats include Giardia duodenalis, Cryptosporidium spp., Cystoisospora spp., and Tritrichomonas foetus. Even though, Entamoeba spp. is rarely reported in cats, it has been recently identified in the stool samples of the feline species in Malaysia. Toxoplasma gondii is often reported in cats and though rarely causes diarrhea, it can be fatal to cats. Most of these protozoa carries a zoonotic risk as well. Currently, there is a lack of updated information on the current prevalence of these gastrointestinal protozoa in Malaysia. Thus, the objectives of this study were to determine the prevalence of these gastrointestinal protozoa in pet and stray cats in Klang Valley, Malaysia; to determine the seroprevalence of Toxoplasma gondii in pet and stray cats in Klang Valley, Malaysia; and to investigate the risk factors associated with protozoan infections. 201 fecal samples and 198 blood samples were randomly collected from pet cats presented to University Veterinary Hospital and stray cats from the local council, Dewan Bandaraya Kuala Lumpur. Among the collected fecal samples, 24 were cultured for T. foetus using InPouch® TF Feline, simple fecal floatation was performed on 44 samples, 58 fecal samples were subjected to Giardia spp. antigen chromatographic immunoassay and all 201 samples to polymerase chain reaction (PCR). PCR was performed to detect Giardia spp., Cryptosporidium spp., Toxoplasma gondii, Tritrichomonas foetus and Entamoeba histolytica. Indirect-ELISA was used to detect Toxoplasma gondii antibody in blood samples collected. Samples were then grouped according to their age, sex, breed and management to study the risk factors associated with the gastrointestinal protozoa infection. In general, the overall prevalence in the cat population in Klang Valley was 50% Cystoisospora spp., 7.9% Giardia duodenalis, 10.4% Toxoplasma gondii and 33% Tritrichomonas foetus. Seroprevalence of Toxoplasma gondii was 5.6% among samples collected. Both Cryptosporidium spp. and Entamoeba spp. failed to be amplified in multiple attempts in our study, thus the molecular epidemiology of these two gastrointestinal protozoa in the cat population in Klang Valley remain unknown. Age, sex, breed and pet cat management showed no significant association with infection with Giardia duodenalis, Toxoplasma gondii and Tritrichomonas foetus in cats (P>0.05). Stray cats showed a significantly higher risk for protozoan infection as compared to pet cats (P<0.05). In conclusion, a high prevalence of gastrointestinal protozoa was detected in the cat population in the Klang Valley. This is alarming due to the clinical importance and zoonotic risk of the protozoa detected.